Antibiotic prophylaxis in veterinary orthopaedic surgery - Budsberg, S. C.; Kirsch, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
Antibiotic prophylaxis is widespread in veterinary and human surgery. Key principles must be followed in case selection, drug choice and administration to ensure maximal effectiveness. More prospective clinical trials in veterinary orthopaedics are needed to better define which patients and which procedures will benefit from antimicrobial prophylaxis.
Keywords: Antibiotics; prophylaxis; orthopaedic surgery